A template for writing radiotherapy protocols. (February 2015) - Nilsson, Per; Ceberg, Crister; Kjellén, Elisabeth; Gagliardi, Giovanna; Blomgren, Klas; Nilsson, Sten; Johansson, Mikael; Glimelius, Bengt
Abstract: Background . Well-specified and unambiguous treatment protocols are essential both for current practice and for the future development of radiation therapy. In order to provide assistance for writing good protocols, irrespective of treatment intention and complexity, up-to-date guidelines are highly desirable. Methods . We have analysed the radiotherapy work-flow, including clinical and physical aspects, such as preparatory imaging, treatment planning, delivery and evaluation, with the aim to outline a consistent framework covering the entire radiotherapy process. Results . Based on the analysis, a recipe-style template for specifying the description of the radiotherapy process has been designed. The template is written in a general format, which allows for modified phrasing, and should be customised for the specific clinical situation and diagnosis, as well as facility resources. Conclusions . The template can be used as a tool to ensure a consistent and comprehensive description of the radiotherapy section of clinical guidelines, care programmes and clinical trial protocols.